A Two-Stage Approach for Resource Allocation and Surgery Scheduling With Assistant Surgeons - Jin Wang; Xin Li; Jing Chu; Kwok-Leung Tsui (IEEE Access, 2020)
The high costs of operating rooms (ORs) make surgery scheduling decisions critical for hospitals, which refer to resource allocations and determining the start time of each surgery. We take into account an important issue that could affect surgery scheduling decisions, ie., assistant surgeons. The operating room scheduling problem is considered as a two-stage problem. The first stage refers to resource allocations, including allocating surgeries into ORs and assigning assistant surgeons to surgeries, while the start time of each surgery is determined in the second stage. The robustness of the model is considered in a tractable way. We develop a bound-based algorithm to solve the model with the objective of minimising the total cost in the two stages. Numerical studies show the good performances of the proposed algorithm. Sensitivity analysis is conducted to examine the effects of the key parameters. An easy-to-implement policy for decisions in the first stage is inspired by the results of the experiments.